Spontaneous Intracranial Hypotension and Epidural Blood Patch: A Report Involving Seven Cases. Issue 3 (May 2013) - Ferraro, F.; Marano, E.; Petruzzi, J.; Tedeschi, E.; Santulli, L.; Elefante, A.
Spontaneous intracranial hypotension is a rare condition caused by spontaneous cerebrospinal fluid leak. It is characterised by orthostatic headache, diffuse pachymeningeal enhancement on brain imaging and low cerebrospinal fluid pressure. Seven patients with spontaneous intracranial hypotension were treated conservatively: of these, four responded to drug treatment and three underwent a lumbar autologous epidural blood patch (EBP). A complete response was obtained in two patients after a single EBP; one patient underwent a second EBP and then became asymptomatic. Clinical improvement coincided with a dramatic reduction of pachymeningeal enhancement. The aetiology and brain imaging findings, and the technique and effectiveness of EBP are discussed.